Endogenous market structure and Partisan competition authorities - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2022)
The so-called excess-entry theorem (Mankiw and Whinston 1986, Suzumura and Kiyono, 1987) establishes conditions guaranteeing that more firms enter a homogeneous Cournotoligopoly in equilibrium than a benevolent government prefers. We generalise the approach and analyse the behaviour of a competition authority, which attaches different weights to the firms' and consumers' payoffs, with welfare-maximisation constituting a special case. The greater the importance of consumers is, the less likely are entry restrictions, whereas a greater relevance of firms makes a monopoly more probable. The nature of entry restrictions also depends on the competition authority's instruments. The essential insights continue to apply if firms are heterogeneous concerning costs and the timing of output choices.
Keywords: D42; D43; D72; L12; L13; L51; 330; Competition Authority; Cournot-Oligopoly; Excessive Entry; Monopoly; Partisan Objective